2019
DOI: 10.1038/s41467-019-12637-0
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric multi-momentum meta-transformer in the visible

Abstract: Metasurfaces as artificially nanostructured interfaces hold significant potential for multi-functionality, which may play a pivotal role in the next-generation compact nano-devices. The majority of multi-tasked metasurfaces encode or encrypt multi-information either into the carefully tailored metasurfaces or in pre-set complex incident beam arrays. Here, we propose and demonstrate a multi-momentum transformation metasurface (i.e., meta-transformer), by fully synergizing intrinsic properties of light, e.g., or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 44 publications
0
70
0
1
Order By: Relevance
“…[20,21] In 1992, it was recognized that light beams with a helical phase structure described by exp(iℓθ), where θ is the azimuthal angle and ℓ is the topological charge of optical vortex, carry an orbital angular momentum (OAM) of ℓℏ per photon. [22,23] Twisted light beams have been applied in various research fields, including optical communication, [3] optical trapping, [24] new forms of imaging systems, [25][26][27] nonlinear material, [28,29] and quantum optics. [30][31][32] As a promising candidate, optical metasurfaces have been used to generate various twisted light beams [33][34][35] and to control the superpositions of twisted light beams.…”
Section: Polarization Detection Using Light's Orbital Angular Momentummentioning
confidence: 99%
“…[20,21] In 1992, it was recognized that light beams with a helical phase structure described by exp(iℓθ), where θ is the azimuthal angle and ℓ is the topological charge of optical vortex, carry an orbital angular momentum (OAM) of ℓℏ per photon. [22,23] Twisted light beams have been applied in various research fields, including optical communication, [3] optical trapping, [24] new forms of imaging systems, [25][26][27] nonlinear material, [28,29] and quantum optics. [30][31][32] As a promising candidate, optical metasurfaces have been used to generate various twisted light beams [33][34][35] and to control the superpositions of twisted light beams.…”
Section: Polarization Detection Using Light's Orbital Angular Momentummentioning
confidence: 99%
“…Two digits of the Arabic numerals from 01 to 26 are used to represent alphabet letters from A to Z in order to achieve encrypting messages. Meanwhile, Jin et al [85] demonstrated a OAM meta-transformer with the capability of transforming the intrinsic phases of OAM (exp(ilħ)) of the incidence light into various distinct patterns in the same plane based on carefully designed phase retrieve method, as shown in Fig. 5c.…”
Section: Oam-multiplexed Holographymentioning
confidence: 99%
“…Ten high order OAM modes can be used to reconstruct ten OAMdependent digits [84]. c An OAM meta-transformer which can reconstruct "0", "3" and "6" by designed three OAM states, respectively [85]. d The principle of vortex and polarization encryption based on proposed metasurfaces.…”
Section: Spectral-and Spatial-multiplexed Metasurfacementioning
confidence: 99%
“…Commonly, a dispersion-less phase modulation method, usually by using the geometric phase, is used. Image multiplexing is divided into in-plane [168][169][170] and out-of-plane [164,[171][172][173][174][175] schemes depending on where those three intensity images appear with respect to one another for a monochromatic illumination. For in-plane image multiplexing, the hologram is encoded such that the images for the three colors (for example, R, G, and B letters in Figure 15E) are located at different positions on the imaging plane [168].…”
Section: Full-color Meta-hologramsmentioning
confidence: 99%